Research on Dynamic Detection Method of Buffer Overflow Vulnerabilities Based on Complete Boundary Test - Li, Zesong; Yang, Hui; Ge, Junwei; Yu, Qinyong (2020 IEEE 6th International Conference on Computer and Communications (ICCC), 2020)
At present, when the device management application programs the devices (such as mobile terminals, Internet of things terminals and devices, etc.), buffer overflow will inevitably occur due to the defects of filter input condition setting, variable type conversion error, logical judgment error, pointer reference error and so on. For this kind of software and its running environment, it is difficult to reduce the false positive rate and false negative rate with traditional static detection method for buffer overflow vulnerability, while the coverage rate of dynamic detection method is still insufficient and it is difficult to achieve full automation. In view of this, this paper proposes an automatic dynamic detection method based on boundary testing, which has complete test data set and full coverage of defects. With this method, the input test points of the software system under test are automatically traversed, and each input test point is analyzed automatically to generate complete test data; driven by the above complete test data, the software under test runs automatically, in which the embedded dynamic detection code automatically judges the conditions of overflow occurrence, and returns the overflow information including the location of the error code before the overflow really occurs. Because the overflow can be located accurately without real overflow occurrence, this method can ensure the normal detection of the next input test point, thus ensuring the continuity of the whole automatic detection process and the full coverage of buffer overflow detection. The test results show that all the indexes meet the requirements of the method and design.